Evaluating the impact of preferential markets on Eswatini SME economy - Makhanya, Mmeli Maphiwa (Graduate School of Business (GSB), 2022)
The study was motivated by the fact that the impact of preferential trade agreements (PTA) on Eswatini SME economies (measured through labour productivity (LP), as well as the perception from SMEs on these markets) remain unknown. Studies conducted in various continents give conflicting findings on the benefit realised by SMEs exporting to PTAs. In analysing the economic effect of PTAs on Eswatini SMEs, the researcher selected variables affecting labour productivity (LP) based on previous literature findings, and gathered SME perceived solutions to improve PTA through interviews. A mixed method approach was employed, where the quantitative aspect employed Cobb-Douglas production function. LP being the dependent variable, the independent categorical variables were capital intensity, size of firm, qualification of directors, age of directors, proportion of revenue obtained from PTA, and dummy variables being technology, networking, capacity building, external financing, family firm, and tax. Qualitative data on the one hand was gathered through interviews and analysed using a thematic analysis model, based on a tripartite approach themes were generated. The quantitative findings through descriptive statistics presented that LP and size of firm as highly volatile, yet all other variables do not show high volatility. This study found that capital intensity, technology, networking, capacity building, and finance have positive effects on LP, with capacity building followed by financial support causing the most significant increase on LP. Firm size, director's qualifications and age, proportion of revenue, family firm, and tax were found to cause a negative growth effect on LP. Through qualitative data, SMEs observed that PTA sustains job opportunities, however, SMEs lament that preferential markets are highly volatile, competitive, and quality driven. Furthermore, lack of access to finance, coupled with high cost of production put SMEs at a disadvantage. Dependence on manual labour rather than technology result in firm size causing a negative growth effect. Internal conflicts and poor policy framework threaten the sustainability of smallholder farmers. SMEs put their hope on policy adjustments, improved ease of doing business with a special focus on increasing trade rather than revenue collections.